Transforming Islamic Education: Madrasah-Based Management Strategies for Academic Excellence - Fatihin, Moh Khoirul; Asnawi, Nur; Tharaba, M Fahim (JURNAL AL-TANZIM, 2023)
This research aims to analyze the implementation of madrasah-based management in improving the quality of education at Madrasah Aliyah Tulungagung from three aspects of management: planning, implementation, and evaluation. This research uses a qualitative case study approach, with research sites at MAN 1 Tulungagung and MAN 2 Tulungagung. Data collection techniques use interviews, documentation, and field observations. The data analysis technique uses the Milles Huberman interactive model, namely data reduction, data display, and data verification. The research results show that the two madrasah have implemented management to improve the quality of madrasah-based education, starting from planning, implementation, and evaluation to create high-achieving Islamic educational institutions. Planning to improve the quality of madrasah-based education reaches level 3, namely representative participation. Implementation of improving the quality of madrasah-based education reaches level 4, namely transformative participation, and evaluation of improving the quality of madrasah-based education reaches level 4, namely transformative participation. This research provides implications regarding the importance of madrasah-based management by involving all parties in managing educational institutions efficiently and effectively.